Risk factors and seroprevalence of asymptomatic human visceral leishmaniasis in an area of intense transmission in Petrolina/PE, Brazil - Barberino, Maiara; Almeida Rodrigues de Souza, Eline; Santos, Yarlen; Amarante, Natália; Silva, Lívia; Claudio Horta, Maurício; Domingues de Faria, Marcelo (Brazilian Journal of Global Health, 2022)
OBJETIVOS: Identificar a soroprevalência de assintomáticos em áreas de transmissão da doença e analisar os fatores de risco ambiental, socioeconômico e demográfico no município de Petrolina/PE, Brasil. MÉTODOS: Foram abordados 92 indivíduos em 19 localidades com casos de LV registrados no Sistema de Informação de Agravos de Notificação (SINAN) entre 2016 e 2017. Em cada visita, foram aplicados dois questionários buscando obtenção de variáveis clínicas, sociais, econômicas e ambientais. Amostras viáveis de sangue coletadas nas visitas (n=90) foram submetidas à Reação de Imunofluorescência Indireta para identificação de anticorpos anti-Leishmania. Para análise dos dados, foram realizados testes estatísticos descritivos utilizando o Software Stata® 14.0. RESULTADOS: A presença de anticorpos foi detectada em 2,2% (2/90) das amostras, no qual um indivíduo apresentava sintomas e o outro foi classificado como assintomático. Não foram identificados fatores de risco relacionados à presença de anticorpos anti-Leishmania. CONCLUSÃO: A identificação de um indivíduo assintomático reforça a importância de ampliar os estudos de prevalência humana em áreas endêmicas. Apesar de prevalência baixa, foi possível identificar um possível caso com manifestação da forma clínica de LV crônica que necessita dos devidos cuidados assistenciais. DESCRITORES: Leishmania, Portador sadio, RIFI. ABSTRACT OBJECTIVES: To identify the seroprevalence of asymptomatic individuals in areas of disease transmission and analyze the environmental, socioeconomic and demographic risk factors in the municipality of Petrolina/PE, Brazil. METHODS: We approached 92 individuals in 19 localities with VL cases recorded in the Information System for Notifiable Diseases (SINAN) between 2016 and 2017. In each visit, two questionnaires were applied seeking to obtain clinical, social, economic and environmental variables. Viable blood samples collected during the visits (n=90) were submitted to the Indirect Immunofluorescence Reaction to identify anti-Leishmania antibodies. For data analysis, descriptive statistical tests were performed using Stata® 14.0 software. RESULTS: The presence of antibodies was detected in 2.2% (2/90) of the samples, in which one individual presented symptoms and the other was classified as asymptomatic. No risk factors related to the presence of anti-Leishmania antibodies were identified. CONCLUSION: The identification of one asymptomatic individual reinforces the importance of expanding human prevalence studies in endemic areas. Despite the low prevalence, it was possible to identify a possible case with manifestation of the clinical form of chronic VL that needs proper care. DESCRIPTORS: Leishmania, Healthy carrier, IFT.